2014
DOI: 10.1186/1471-2261-14-55
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of positive response to cardiac resynchronization therapy

Abstract: BackgroundApproximately 30% of patients treated with cardiac resynchronization therapy (CRT) do not achieve favourable response. The purpose of the present study was to identify echocardiographic and clinical predictors of a positive response to CRT.MethodsThe study included 82 consecutive heart failure (HF) patients in New York Heart Association (NYHA) functional class III or IV with left bundle branch block (LBBB), QRS duration ≥ 120 ms and left ventricular ejection fraction (LVEF) ≤ 35%. Statistical analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 26 publications
1
14
2
Order By: Relevance
“…In addition, the design of the study, baseline NYHA class, and LVDV were also shown to be the predictors of response to CRT, and these factors might influence the improvement in LVEF. 21,22 However, the results of our subgroup analyses found the improvement in LVEF in the Tri-V pacing group was not affected by these factors except for the duration of QRS. The benefits on the improvement in Tri-V pacing were significant in patients with QRS duration ≥155 ms, but not in patients with QRS duration <155 ms.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…In addition, the design of the study, baseline NYHA class, and LVDV were also shown to be the predictors of response to CRT, and these factors might influence the improvement in LVEF. 21,22 However, the results of our subgroup analyses found the improvement in LVEF in the Tri-V pacing group was not affected by these factors except for the duration of QRS. The benefits on the improvement in Tri-V pacing were significant in patients with QRS duration ≥155 ms, but not in patients with QRS duration <155 ms.…”
Section: Discussionmentioning
confidence: 67%
“…Therefore, the baseline duration of QRS might also affect the result of our study. In addition, the design of the study, baseline NYHA class, and LVDV were also shown to be the predictors of response to CRT, and these factors might influence the improvement in LVEF . However, the results of our subgroup analyses found the improvement in LVEF in the Tri‐V pacing group was not affected by these factors except for the duration of QRS.…”
Section: Discussionmentioning
confidence: 76%
“…Goldenberg et al demonstrated that LV end-diastolic volume (LVEDV) is associated with CRT response [10]. In addition, Rinkuniene et al reported that LVEDD < 75 mm is the strongest independent predictor of CRT response [11]. Díaz-Infante et al also found that LVEDD ≥ 75 mm is an independent predictor of nonresponse to CRT [12].…”
Section: Discussionmentioning
confidence: 99%
“…According to echocardiographic criteria, patients who had an increase of LVEF ≥5% after 6 months of CRT treatment was defined as responders to CRT [13], patients with an increase of LVEF < 5% were categorized as non-responders. In current study, subjects were divided into discovery set (n = 51, 27 responders and 24 nonresponders) and validation set (n = 54, 36 responders and 18 non-responders).…”
Section: Study Subjectsmentioning
confidence: 99%